"Counselor in Your Pocket": Youth and Provider Perspectives on a Mobile Motivational Intervention for Marijuana Use. (1st January 2014) - Shrier, Lydia A.; Rhoads, Amanda M.; Fredette, Meghan E.; Burke, Pamela J.
Abstract : Previous interventions for marijuana use have been administered out of the real-life contexts in which use occurs. In 2010, we interviewed youth aged 15–24 years who use marijuana frequently ( n = 8) and providers who treat them ( n = 6) on the acceptability and utility of a mobile intervention involving momentary self-monitoring of use-related contexts and responsive motivational messaging following clinic-based brief motivational enhancement therapy. Thematic analysis was used to examine youth and provider perspectives on the mobile intervention. Results suggest that mobile technology is a promising tool for brief interventions to reduce youth marijuana use and warrants further development.